2015
DOI: 10.1093/europace/euu310
|View full text |Cite
|
Sign up to set email alerts
|

3D delayed-enhanced magnetic resonance sequences improve conducting channel delineation prior to ventricular tachycardia ablation

Abstract: 3D scar reconstruction using images from 3D-GRE sequence improves the overall delineation of CC prior to VT ablation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
119
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 121 publications
(125 citation statements)
references
References 22 publications
3
119
0
3
Order By: Relevance
“…All LGE-CMR images were analysed using a previously described technique 13. Briefly, full LV volume was reconstructed in the axial orientation and the resulting images were processed with ADAS-VT software (Galgo Medical, Barcelona, Spain).…”
Section: Methodsmentioning
confidence: 99%
“…All LGE-CMR images were analysed using a previously described technique 13. Briefly, full LV volume was reconstructed in the axial orientation and the resulting images were processed with ADAS-VT software (Galgo Medical, Barcelona, Spain).…”
Section: Methodsmentioning
confidence: 99%
“…35, 36 Other recent studies have used segmented myocardial shells to delineate layers of core as distinct from border zones and thereby locate border zone channels that correlate with VT isthmuses identified by electroanatomic pacemapping. 37, 38 …”
Section: Cmr Assessment Of Myocardial Scar and Scar Heterogeneitymentioning
confidence: 99%
“…Multiple important studies have been reported within the last 12 months documenting the importance and increased utilization of VT ablation. Despite several remarkable technical and technological improvements and innovations such as use of image integration, 26 novel ablation electrodes, 27,28 forcesensing technologies, 29 or ultra-high density mapping, 30 the relatively high recurrence rate of any VT after catheter ablation in patients with VT and structural heart disease remains a key challenge. As evident from recent multi-centre data, non-inducibility of any VT at the end of the ablation is probably the best endpoint for the procedure and should be targeted.…”
Section: Ventricular Arrhythmias and Sudden Cardiac Deathmentioning
confidence: 99%